Bioassay assessment of mine pit lake water for aquaculture and biodiversity conservation - Neil, Luke L (Curtin University, 2007)
For decades, researchers have been working to better understand the effects of acid and metal toxicity to aquatic organisms and to develop ways to effectively mitigate these detrimental effects. Acid mine drainage (AMD) causes environmental pollution that affects many countries having historic or current mining industries. Both surface and underground mining have the potential to create AMD and therefore adversely affect the local and adjacent environments. Through malignant mining and farming practices, damming rivers and the changing climate, surface freshwater resources are rapidly being reduced in Australia. Mine pit lakes offer a large freshwater resource that if managed correctly may sustain significant environmental, social and economic benefits from selected end uses for the future. However, assessment of mine pit lakes needs to be achieved to validate end use options. The Collie Basin located in the southwest of Western Australia is a coal mining area with many abandoned open cast mines (OCM). Some of these OCM have filled with water forming mine pit lakes that are affected by AMD. The result is large freshwater bodies with moderate to high concentrations of metals and a low pH. High concentration of metals combined with low pH is of environmental concern to both the aquatic and terrestrial ecosystem. Nevertheless, remediation techniques for AMD are available and applicable to these acidic lakes. However, the lakes in the Collie Basin are low in sulphatic compounds, therefore, restricting the use of the most common remediation treatment of bioremediation with sulphate reducing bacteria. Three remediation treatments were assessed for there efficacy in toxicity amelioration to three mine pit lakes. The treatments assessed were Limestone addition, phosphorus addition and a Rapid Catalytic Oxidation (RCO) treatment.Toxicity assessment was achieved by means of comparing physico-chemical data to guideline trigger values and biological assessment. Biological assessment was achieved with three commonly used but ecologically and geographically relevant species. The bioassay species were the alga Chlorella protothecoides, the crustacean Ceriodaphnia cf dubia and the protozoa Tetrahymena thermophila. Aquaculture is being trialled adjacent to one of the pit lakes in limestone treated mine pit lake water. Therefore, the aquaculture fish species Bidyanus bidyanus early life stages were also used to assess residual toxicity from treated mine pit lake water. Limestone remediation of pit lake water demonstrated good reduction of dissolved metal concentrations with the exception of Zn and the ability to increase pH to circum-neutral. Biological assessment of limestone treated pit lake water showed that toxicity was removed to the three bioassay species and to the aquaculture species B. bidyanus early life stages. A larger field- scale mesocosm experiment with limestone treatment in situ is recommended. Assessment of the mesocosm experiment with biological and chemical analysis will confirm the efficacy of this treatment for full scale use.